Antidumping policy in the European Community: Political discretion or technical determination - Angelika Eymann; Ludger Schuknecht (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
This paper demonstrates the prominent role of antidumping laws as an Instrument of endogenous trade policy in the EC. In contrast with the US where dumping is subject to technical determination, the EC application of antidumping laws reflects political discretion and influence.
Keywords: 330